Chinese Syllable and Phoneme Identification in Noise and Reverberation - PENG, Jianxin (Archives of Acoustics, 2014)
Chinese is a tonal language, which differentiates it from non-tonal languages in the Western countries. A Chinese character consists of an initial, a final, and a tone. In the present study, the effects of noise and reverberation on the Chinese syllable, initial, final, and tone identification in rooms were investigated by using simulated binaural impulse responses through auralization method. The results show that the syllable identification score is the lowest, the tone identification score is the highest, and the initial identification scores are lower than those of the final identification under the same reverberation time and signal-to-noise ratio condition. The Chinese syllable, initial, and final identification scores increase with the increase of signal-to-noise ratio and decrease of the reverberation time. The noise and reverberation have insignificant effects on the Chinese tone identification scores under most room acoustical environments. The statistical relationship between the Chinese syllable articulation and phoneme articulation had been experimentally proved under different noise and reverberation conditions in simulated rooms.